2013
DOI: 10.1177/0312896213503665
|View full text |Cite
|
Sign up to set email alerts
|

Congruence of leader self-perceptions and follower perceptions of authentic leadership: Understanding what authentic leadership is and how it enhances employees’ job satisfaction

Abstract: Congruence of leader self-perceptions and follower perceptions of authentic leadership: Understanding what authentic leadership is and how it enhances employees' job satisfaction AbstractWe propose and empirically test a multilevel model of cross-level interactions between leader self-perceptions (team level) and follower perceptions of authentic leadership on job satisfaction. Data from 24 supervisors and 171 team members were used. Applying hierarchical linear modeling, we found that follower perceptions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
48
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 51 publications
(114 reference statements)
7
48
0
1
Order By: Relevance
“…Most consistently, relationships with followers’ trust, engagement and satisfaction measures were found3, 4, 27, 28, 29, 30 ) . Research focusing on negative follower outcomes is still in its infancy.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Most consistently, relationships with followers’ trust, engagement and satisfaction measures were found3, 4, 27, 28, 29, 30 ) . Research focusing on negative follower outcomes is still in its infancy.…”
Section: Introductionmentioning
confidence: 81%
“…This is quite astonishing as authentic leadership has been promised to be the essence of any positive form of leadership3, 4 ) . Gaining insights into how authentic leadership unfolds its positive energy in the workplace means to gain new insights into other leadership styles as well.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Considering literature suggesting that high (low) self-other agreement (SOA) in leadership measurement is associated with better (worse) leadership outcomes (Atwater and Yammarino 1997; Cerne et al, 2013;de Vries 2012;Fleenor et al 2010), SOA in the measure of humility was also explored in relation to balanced processing and the perceived impact on team effectiveness.…”
Section: Post Hoc Analysismentioning
confidence: 99%
“…However, one study conducted by Szell and Henderson (1997) found that rating congruence on measures of performance and motivation was positively related to employee job satisfaction and organizational commitment. More recently, one study utilized the SOA research paradigm to assess congruence on measures of leadership authenticity and employee outcomes and found congruence significantly related to job satisfaction (Černe, Dimovski, Marič, Penger, & Škerlavaj, 2014).…”
Section: Family-supportive Supervisor Behaviors the First Decade Of mentioning
confidence: 99%